2006
DOI: 10.1063/1.2364457
|View full text |Cite
|
Sign up to set email alerts
|

Microdroplet deposition of copper film by femtosecond laser-induced forward transfer

Abstract: Phase change mechanisms during femtosecond laser pulse train ablation of nickel thin filmsCopper microdroplets were deposited onto a quartz substrate by the laser-induced forward transfer ͑LIFT͒ using laser pulses of 148 fs at a center wavelength of 775 nm. The droplets with 2 -3 m diameters were transferred at a laser pulse energy slightly above the threshold at which the copper film could be removed completely. The droplet formation was a result of the blow-off of a molten film from the quartz substrate by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 15 publications
2
38
1
Order By: Relevance
“…This method is based on laser-induced transfer of molten nanodroplets initiated by tightly focused laser pulses. A similar approach has already been applied to the controlled fabrication of metal nanoparticles [27][28][29][30][31][32] . A more sophisticated method using a ring-shaped femtosecond laser intensity distribution has been recently applied for the generation of single Si nanoparticles from bulk Si targets 17 .…”
Section: Resultsmentioning
confidence: 99%
“…This method is based on laser-induced transfer of molten nanodroplets initiated by tightly focused laser pulses. A similar approach has already been applied to the controlled fabrication of metal nanoparticles [27][28][29][30][31][32] . A more sophisticated method using a ring-shaped femtosecond laser intensity distribution has been recently applied for the generation of single Si nanoparticles from bulk Si targets 17 .…”
Section: Resultsmentioning
confidence: 99%
“…with the donor layer thickness d = 100 nm, the specific heat capacity C p ¼ 2:5 Á 10 6 J=ðm 3 KÞ, density q ¼ 19;300 kg=m 3 , latent heat of fusion L m ¼ 0:6 Á 10 5 J=kg, and reflectivity R ¼ 0:6 for the given wavelength of 515 nm wavelength [26,27]. It is found that the perimeter fluence level of F ¼ 0:24 J=cm 2 is sufficient to melt the donor layer, which is in accordance with the experimental results.…”
Section: Single-pulse Processmentioning
confidence: 99%
“…Laser-induced forward transfer (commonly abbreviated to LIFT) is a direct-write technique that allows the selective transfer of many materials on a micrometer scale [1][2][3][4][5], including liquids [6] and living cells [7,8]. In the LIFT process, a thin film serves as a donor material that is to be transferred, which is referred to as the donor layer, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, controlled deposition is often achieved in liquid phase. In this regime, for LIFT just above the ejection threshold fluence, a single spherical deposit is observed [18,42,49]. At intermediate ejection fluence levels, deposition of a torus-like shape is observed [18], which indicates that the droplet solidified in a spread-out state.…”
Section: Research Objectivesmentioning
confidence: 92%
“…So far, application of pure-metal LIFT for 3D direct-write has been limited to the deposition of single metal droplets [18,42,49], conductive lines or tracks [10,19], and the deposition of nanoparticles [50]. This is because two challenging requirements have to be simultaneously fulfilled for consistent deposition: the impact location of a single droplet has to be limited to the previously deposited droplet's impact area, and good adhesion between the deposited droplets is required.…”
Section: Research Objectivesmentioning
confidence: 99%